MELTING PARAMETERS OF DNA COMPLEXES WITH SEVERAL INTERCALATORS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Comparative study of DNA complexes with acridine orange (AO), ethidium bromide (EtBr) and methylene blue (MB) has been carried out at 0.02 M ionic strength of solution in 0 < r $≤$ 0.33, r = [ligand] / [DNA] range. The values of changes of melting parameters ($δ(1/T_m)$ and $δ(Δ T/T_m^ 2))$ of these complexes were determined. From the obtained data it was revealed that the dependence of $δ (1/T_m)$ enhances in the whole interval of change of r for three ligands, while the dependence of $δ(Δ T/T_m^ 2)$ rises at relatively low values of r and comes out to plateau in the case of AO and MB; in the case of EtBr this dependence takes bell-like form.
Keywords: DNA, acridine orange, ethidium bromide, intercalation, methylene blue, melting curve